2000
DOI: 10.1016/s1083-8791(00)70013-9
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of tuberculosis in adult allogeneic stem cell transplant recipients in Turkey

Abstract: In general, tuberculosis (Tb) is rarely seen in allogeneic stem cell transplant (alloSCT) recipients, but this observation has been challenged in developing countries such as Turkey, where Tb infection is more prevalent than in Europe and the US. In this retrospective study, we report on the incidence of Tb infections in 351 alloSCT recipients at 4 bone marrow transplantation units in Turkey over the last 10 years. The frequency of Tb in alloSCT recipients after allografting (5 of 351) was far greater than tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 13 publications
2
60
1
4
Order By: Relevance
“…[40][41][42] However, in endemic countries, high incidence up to 5% has been reported. 43,44 Although prevalence of tuberculosis has dramatically decreased nowadays, Korea is still a tuberculosis-endemic country. According to the seventh nationwide tuberculosis survey in Korea, 1995, prevalence of active tuberculosis is 1032/100 000.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42] However, in endemic countries, high incidence up to 5% has been reported. 43,44 Although prevalence of tuberculosis has dramatically decreased nowadays, Korea is still a tuberculosis-endemic country. According to the seventh nationwide tuberculosis survey in Korea, 1995, prevalence of active tuberculosis is 1032/100 000.…”
Section: Discussionmentioning
confidence: 99%
“…21,24 Despite their pathogenicity among a wide variety of hosts, NTM are uncommon pathogens in alloSCT recipients according to published reports. 8,9,12,15,25 Table 2 includes a comparison of the patients reported here and those from other series. The rates of positive cultures for NTM and NTM infection were 5-to 20-fold higher at our institution than at other centers.…”
Section: Discussionmentioning
confidence: 99%
“…Both Mycobacterium tuberculosis and nontuberculous mycobacteria (NTM) are well-described pathogens in alloSCT recipients. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, distinguishing infection from colonization by NTM such as Mycobacterium avium complex (MAC) can be difficult, as infection by organisms other than NTM and noninfectious conditions such as graft-versus-host disease (GvHD) can mimic NTM infection in alloSCT recipients. Formal diagnostic criteria for NTM infection ( Figure 1) have been established by the Centers for Disease Control and Prevention (CDC) and the American Thoracic Society but remain controversial.…”
mentioning
confidence: 99%
“…21 Studies from developing countries, including Turkey and Hong Kong, have reported incidences varying between 1 and 12%. [22][23][24] In view of the low incidence in India, INAH prophylaxis during BMT may not be essential.…”
Section: Discussionmentioning
confidence: 99%